A CRISPR‐Cas12a‐derived biosensor enabling portable personal glucose meter readout for quantitative detection of SARS‐CoV‐2. Issue 4 (4th February 2021) - Huang, Di; Shi, Zhuwei; Qian, Jiajie; Bi, Ke; Fang, Mengjun; Xu, Zhinan
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has spread rapidly throughout the whole world and caused significant difficulties in the prevention and control of the epidemic. In this case, several detection methods have been established based on nucleic acid diagnostic techniques and immunoassays to achieve sensitive and specific detection of SARS‐CoV‐2. However, most methods are still largely dependent on professional instruments, highly trained operators, and centralized laboratories. These limitations gravely diminish their practicality and portability. Herein, a clustered regularly interspaced short palindromic repeats (CRISPR) Cas12a based assay was developed for portable, rapid and sensitive of SARS‐CoV‐2. In this assay, samples were quickly pretreated and amplified by reverse transcription recombinase‐aided amplification under mild conditions. Then, by combining the CRISPR Cas12a system and a glucose‐producing reaction, the signal of the virus was converted to that of glucose, which can be quantitatively read by a personal glucose meter in a few seconds. Nucleocapsid protein gene was tested as a model target, and the sensitivity for quantitative detection was as low as 10 copies/μl, which basically meet the needs of clinical diagnosis. In addition, with the advantages of lower material cost, shorter detection time, and no requirement for professional instrument in comparison with quantitative reverse transcription‐polymerase chain reaction, this assay is expected to provide a powerful technical support for the early diagnosis and intervention during epidemic prevention and control. Abstract : A novel strategy combining CRISPR Cas12 system and magnetic beads‐based biosensors for portable and quantitative detection of SARS‐CoV‐2 by personal glucose meter was developed in this study, which shows the advantages of lower material cost, shorter detection time, and no requirement for professional instrument in comparison with qRT‐PCR. This platform provides potential applications for the early diagnosis and intervention during epidemic prevention and control.